405 Role of Glycans in Cancer Associated Fibroblast-Derived Exosome Immunoregulation. (April 2022) - Anderson, Johnathon D.; Nolta, Jan; Farwell, D. Gregory; Birkland, Andrew; Van de Water, Judy; Carraway, Kermit; Lebrilla, Carlito
Abstract : OBJECTIVES/GOALS: To identify the role of sialoglycans in the mechanisms underlying cancer-associated fibroblast-derived exosomes (CAFEX) immuno-regulatory properties. The central hypothesis is that CAFEX manipulates the immune response to allow immunoevasion and glycomic approaches can identify the signaling factors involved. METHODS/STUDY POPULATION: Cancer associated fibroblasts (CAFs) were isolated from primary head and neck tumors, expanded, characterized and cryopreserved prior to experimentation and isolation of CAFEX. Sialoglycan expression was determined using lectin-specific staining of cells and bead-captured CAFEX in combination with flow cytometry analysis. Siglec expression and expression of M2-macrophage markers were also determined by flow cytometry analysis and cytokine bead arrays. Inhibition studies involved either the enzymatic removal of cell-surface sialoglycans or alternatively, a specific small molecule analog inhibitor of sialoglycan transferases. RESULTS/ANTICIPATED RESULTS: Both CAFs and CAFEX expressed abundant levels of cell-surface sialoglycans. CAFEX induced an M2-macrophage phenotype in primary monocytes, based on surface marker expression and cytokine secretion profiles. The induction of the M2 phenotype in macrophages was attenuated upon the removal of sialoglycans from the surface of CAFEX either by enzymatic removal or via a small molecule inhibitor. CAFEX were also able to directly bind members of the Siglec family, which are sialoglycan specific lectin receptors expressed on immune cells, including macrophages. DISCUSSION/SIGNIFICANCE: Collectively, these studies suggest that surface presentation of sialoglycans by CAFEX may induce an immunosuppressive phenotype in monocytes/macrophages. Consequently, this may be a novel mechanism by which cells within the tumor bed facilitate immunoevasion during tumor progression.